The Balinese Unicode Text Processing - Imam Habibi; Rinaldi Munir (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2006)
In principal, the computer only recognizes numbers as the representation of a character. Therefore, there are many encoding systems to allocate these numbers although not all characters are covered. In Europe, every single language even needs more than one encoding system. Hence, a new encoding system known as Unicode has been established to overcome this problem. Unicode provides unique id for each different characters which does not depend on platform, program, and language. Unicode standard has been applied in a number of industries, such as Apple, HP, IBM, JustSystem, Microsoft, Oracle, SAP, Sun, Sybase, and Unisys. In addition, language standards and modern information exchanges such as XML, Java, ECMA Script (JavaScript), LDAP, CORBA 3.0, and WML make use of Unicode as an official tool for implementing ISO/IEC 10646. There are four things to do according to Balinese script: the algorithm of transliteration, searching, sorting, and word boundary analysis (spell checking). To verify the truth of algorithm, some applications are made. These applications can run on Linux/Windows OS platform using J2SDK 1.5 and J2ME WTK2 library. The input and output of the algorithm/application are character sequence that is obtained from keyboard punch and external file. This research produces a module or a library which is able to process the Balinese text based on Unicode standard. The output of this research is the ability, skill, and mastering of 1. Unicode standard (21-bit) as a substitution to ASCII (7-bit) and ISO8859-1 (8-bit) as the former default character set in many applications. 2. The Balinese Unicode text processing algorithm. 3. An experience of working with and learning from an international team that consists of the foremost experts in the area: Michael Everson (Ireland), Peter Constable (Microsoft US), I Made Suatjana, and Ida Bagus Adi Sudewa.